Analysis of Factors Influencing Corporate Social Responsibility Disclosure moderated by Profitability in Energy Companies - Euriver Zega; Bambang Satriawan; Robin (Jurnal Akuntansi, 2025)
This research was conducted to assess the contribution of company size, Good Corporate Governance, and leverage to Corporate Social Responsibility practices, as well as evaluate the role of profitability as a moderator. A total of 11 energy sector companies were used as observation units in this study that have gone public and registered on the IDX from 2019 to 2023, with a total of 55 observations. The analysis was carried out through the application of panel data regression analysis and moderation interaction tests. Data analysis in this study shows that the size of the company, the portion of shares owned by the institution and management, and the role of the audit committee do not contribute significantly to CSR disclosure. On the contrary, the board of commissioners and leverage have proven to have a significant positive effect. Profitability acts as a moderator that weakens the influence of business scale aspects, managerial shareholding, and board of commissioners' authority, but strengthens the impact of the existence of an audit committee on corporate social responsibility disclosure. No moderation effect was found on the relationship between institutional ownership and leverage and CSR. The findings of this study indicate that the role of profitability moderation is selective, depending on the aspects of corporate governance and financial structure.